2017
DOI: 10.1167/tvst.6.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Morphologic Classification of Pediatric Cataract Using Slit-Lamp-Adapted Photography

Abstract: PurposeTo investigate the feasibility of pediatric cataract monitoring and morphologic classification using slit lamp–adapted anterior segmental photography in a large cohort that included uncooperative children.MethodsPatients registered in the Childhood Cataract Program of the Chinese Ministry of Health were prospectively selected. Eligible patients underwent slit-lamp adapted anterior segmental photography to record and monitor the morphology of their cataractous lenses. A set of assistance techniques for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
(80 reference statements)
1
8
1
Order By: Relevance
“…In a recent study, Long et al (2017) reported a prevalence of 32.9% of total cataracts, 30.4% -nuclear cataracts, anterior polar -8%, posterior polar -13.5% and lamellar 9.6% [21]. Our results are similar, especially regarding the prevalence of total cataract -28%, lamellar -16% (the most frequent type reported in literature) and nuclear 11%.…”
Section:  Discussionsupporting
confidence: 85%
“…In a recent study, Long et al (2017) reported a prevalence of 32.9% of total cataracts, 30.4% -nuclear cataracts, anterior polar -8%, posterior polar -13.5% and lamellar 9.6% [21]. Our results are similar, especially regarding the prevalence of total cataract -28%, lamellar -16% (the most frequent type reported in literature) and nuclear 11%.…”
Section:  Discussionsupporting
confidence: 85%
“…Third, images used to train the telehealth module are acquired through slit-lamp photography. Therefore, assistances (e.g., strap 30 ) would be required for the uncooperative infants during the photography process. Fourth, the duration of self-controlled test is relatively short (one and four months).…”
Section: Discussionmentioning
confidence: 99%
“…The fine dots of the ring were located in the peripheral cortex. These changes reminisce of supranuclear cataracts in Alzheimer's disease 49 or blue‐dot opacities in humans, 50 which are not well understood. Recently, anterior segment ocular coherence tomography revealed small dot opacities in lenses of individuals with Down syndrome 51 .…”
Section: Discussionmentioning
confidence: 99%